STATISTICS AND DATABASES IN ROAD SAFETY PROBLEM - Knutelska, Marta; Sustekova, Daniela (Doprava a spoje, 2012)
Even though the number of road fatalities in the EU was almost halved in the past decade, 34 500 people were killed on EU roads in 2009. Initiatives in the area of technology, enforcement, education and particular attention to vulnerable road users will be key to drastically reduce these losses of life even further. The White paper on transport published in 2011, stresses the critical role played by road safety problem. The quality, accessibility and reliability of transport services will gain increasing importance in the coming years, inter alia due to the ageing of the population and the need to promote public transport.